A population-based study examining emergency department use in the 12 months following a release from imprisonment in New Zealand. - Malinowski, Natalia; Davie, Gabrielle; Cunningham, Ruth; Crengle, Sue (International Journal of Population Data Science, 2026)
Imprisonment has been linked to poor mental and physical health outcomes with the period following release identified as being particularly challenging. This population-based study examined emergency department (ED) utilisation in the 12 months following a release from imprisonment in New Zealand in 2018. Using national linked health and justice administrative datasets, demographic, incarceration, and diagnostic patterns in ED use post-release were examined. Of 13,686 individuals, 35% presented to the ED at least once, making up 10,734 ED presentations. Those aged 17-24 were the age group most likely to have an ED presentation (38%) and women were more likely than men to present to EDs over 12 months (41% vs 34%). Of the ED presentations, 3,897 (36%) resulted in 3+ hours of treatment in the ED or an inpatient ward, counted as a long-term ED (LT-ED) event. Those released from remand were 1.23 times (95% CI 1.15-1.31) more likely to have a LT-ED event compared to those released from prison. Thirty-eight percent of the LT-ED events were due to injuries; of which assault was the most common external cause. There were high rates of both ED presentations and LT- ED events in the first week after release. When comparing to literature, this cohort presented to the ED approximately 4 times more than the general NZ population. These findings demonstrate the significant health needs of individuals post-imprisonment and emphasise the need to prioritise those released from remand facilities within public health policy, research and practice.